CONSTRUCTING LESSONS ACCORDING TO FEDERAL STATE EDUCATIONAL STANDARDS (FSES) - A. P. Usol’tsev; E. P. Antipova (Образование и наука)
Introduction. Achievement of educational outcomes designated in the Federal State Educational Standards (FSES) of the system of general education is an urgent problem of public schools. The analysis of the existing guidelines of their realization in the course of the lesson shows that they are often declarative or imperative in nature, which makes it impossible for teachers to use them in their practical activity. What is changed is the rhetoric and terminology, but the essence remains the same, or the changes are hasty, premature and are implemented without taking into account the concrete situation. As a result, they do not lead to the accomplishment of the goal set in the new educational standards. The aims of the article consist in presenting a generalized practically realizable construct of a lesson which would provide the teacher with an algorithm of lesson planning in accordance with the goal of the Federal State Educational Standards. Methodology and research methods. The article offers analysis and synthesis of the normative documentation (Federal State Educational Standards), and of the content of scientific-methodological works and scientific publications dealing with practical lesson constructing. Results and scientific novelty. The article analyzes various lesson constructs suggested by theoretical and practical educationalists aimed at accomplishment of the goals designated in the Federal State Educational Standards. The authors come to the conclusion that in their practical activity, teachers often set inadequate lesson aims and thus fail to achieve the subject outcomes, which is in princi pal contrary to the systemic activity-oriented approach upon which these standards are based. The article describes a general algorithm of a lesson constructing which will allow the teacher to algorythmize and optimize the process of lesson preparation according to the requirements of the FSES of the system of general education. Practical significance. It is shown that such constructing makes it possible to achieve not only subject but also meta-subject and personal results.